The conquest : the story of a Negro pioneer - Micheaux, Oscar, 1884-1951 (University of Nebraska Press, 1994)
The novel portrays the aspirations and struggles of a black homesteader named Oscar Devereaux. Born on a small farm near Cairo, Illinois, one of thirteen children, Devereaux leaves home to work in the Chicago stockyards and finally graduates to the job of porter in a Pullman railway car. He is persoable, industrious, and frugal with a purpose. After saving $2,500, Devereaux goes to South Dakota and buys land. His object is not speculation for quick profit but the cultivation of property he can call his own. He plows and sows and sweats, and by the age of twenty-five has reaped an estate worth $20,000. Success is sweet, self-respect is sweeter. But if the calamities he is exposed to as a homesteader are severe, so are those brought on by marriage to the passive daughter of a dominating preacher.
Originally published: Lincoln, Neb., Woodruff Press, 1913.
Keywords: Micheaux, Oscar, -- 1884-1951 -- Fiction.; Micheaux, Oscar, -- 1884-1951; Frontier and pioneer life -- South Dakota -- Fiction.; African American pioneers -- South Dakota -- Fiction.; South Dakota -- Fiction.; Pionniers noirs américains -- Dakota du Sud -- Romans, nouvelles, etc.; Dakota du Sud -- Romans, nouvelles, etc.; FICTION -- Westerns.; African American pioneers; Frontier and pioneer life; South Dakota; English.; Languages & Literatures.; American Literature.; novels.; Autobiographical fiction; Fiction; Novels; Pastoral fiction; Western fiction; Pastoral fiction.; Western stories.; Autobiographical fiction.; Western fiction.; Novels.; Fiction.; Romans pastoraux.; Romans.